SURVEY ON THE RATE AND ANTIBIOTIC RESISTANCE OF KLEBSIELLA PNEUMONIAE IN PATIENTS TREATED AT TWO DEPARTMENTS - INTERNAL INTENSIVE CARE UNIT AND SURGICAL INTENSIVE CARE UNIT - MILITARY HOSPITAL 175 - Nguyen Thi , Trang; Le Thuy , Duong; Tran Khanh , Hoang; Nguyen Ngoc Đang, Khoa; Pham Thi , Huyen; Huynh Quoc , Huy; Nguyen Thi Bich , Thuy; Dinh Thi Ngan, Ha (Tạp chí Y Dược Thực hành 175, 2024)
Background: Strains of K. pneumoniae that produce extended-spectrum β-lactamase (ESBL) and carbapenemases (CARB) are becoming more common and present a significant challenge in treating hospital-acquired infections, especially in Intensive Care Units (ICU). Objectives: To describe the characteristics of K. pneumoniae infections and antibiotic resistance (phenotypic and genotypic) in patients treated at two departments: the Internal Intensive Care Unit (A12.1) and the Surgical Intensive Care Unit (A12.2) of Military Hospital 175. Subjects and Methods: A retrospective study on 235 strains of K. pneumoniae isolated from clinical specimens of patients treated in Intensive Care Units (ICU). Results: There were 157 strains of K. pneumoniae producing CARB (70.1%) and 79 strains (35.3%) producing ESBL and CARB. Among the 21 strains analyzed for drug resistance genes: 6 strains (28.6%) carried one gene, 14 strains (66.7%) carried two genes, and especially, one strain carried 3 genes; NDM was the most commonly popular gene. The antibiotic resistance rates of K. pneumonia strains were high: Imipenem 65.4% - 77.4%, Meropenem 64.7% - 79.2%, Amikacin 24.1% - 56%, Ceftazidime-Avibactam 61.5% - 71.8%, and Colistin 9.3% - 44.7%. Conclusions: The rates of K. pneumoniae-producing ESBL and CARB were relatively high. Strains isolated in the Internal Intensive Care Unit showed higher antibiotic resistance rates than those in the Surgical Intensive Care Unit (statistically significant difference with p<0.05 for Aminoglycosides and Colistin). However, the antibiotic resistance rates remained high in both departments, with a particularly rapid increase in resistance to Carbapenem, Colistin, and new antibiotics like Ceftazidime- Avibactam.